Adding functionality to milk-based protein: Preparation, and physico-chemical characterization of β-lactoglobulin-phenolic conjugates. (15th February 2018) - Abd El-Maksoud, Ahmed A.; Abd El-Ghany, Ismail H.; El-Beltagi, Hossam S.; Anankanbil, Sampson; Banerjee, Chiranjib; Petersen, Steen V.; Pérez, Bianca; Guo, Zheng
Highlights: β-Lactoglobulin-caffeic acid conjugate (βLg-CA) is prepared via one-pot reaction. An optimal coupling of 8 mol caffeic acid to 1 mol βLg is obtained at pH 6. DPPH activity of βLg-CA increases as the number of CA coupling increases. βLg-CA at pH 6 shows superior antioxidant property compared to βLg/CA mixture. The βLg-CA bioconjugates are more thermostable than native βLg. Abstract: Multi-functional phenolic emulsifiers were prepared by covalently coupling β-Lactoglobulin (βLg) to caffeic acid (CA) using crosslinker chemistry at different pH conditions (pH 2.5, 6.0, and 8.5). The resulting bioconjugates were characterized by MALDI-TOF MS, differential scanning calorimetry (DSC), fluorescence-quenching, infrared and circular dichroism spectroscopies. Furthermore, the emulsifying and antioxidant properties of βLg-CA conjugates were evaluated and compared to native β-Lactoglobulin and the non-covalent β-lactoglobulin/caffeic complex (βLg/CA). Results showed: 1) An optimal molar ratio (8:1) of caffeic acid to βLg was obtained at pH 6; 2) DPPH activity of βLg-CA increases as the number of CA units coupled increases; 3) βLg-CA conjugates displayed comparable or superior water solubility than native βLg and βLg/CA. Moreover, DSC results showed that coupling of CA with βLg significantly increased the thermal stability of βLg. In summary, βLg-CA conjugates can act as effective antioxidant emulsifiers and stabilizers and may find application in food and cosmetic industries.